First Copper(Ii) Phase M?0.2mn0.8ps3·0.25h2o and Analogous M? = Coii, Niii and Znii Materials Obtained by Microwave Assisted Synthesis - Venegas-Yazigi, D; Venegas-Yazigi, D (Royal Society of Chemistry, 2015)
M′0.2Mn0.8PS3·0.25H2O materials are obtained by a mild microwave assisted reaction (M′ = CoII, NiII, CuII, ZnII), which permitted us to obtain the first copper(ii) bimetallic phase. All these materials have a lower energy gap and antiferromagnetic interactions with lower values of the Weiss constant, than that of the pristine phase MnPS3. © The Royal Society of Chemistry.